INNOVATIVE DEVELOPMENT OF UKRAINE AND IVANO-FRANKIVSK IN THE WAR PERIOD - Petryna , M. Y.; Stelmaister М.-V. А.; Tarayevska , L. S. (The actual problems of regional economy development, 2024)
The topic of the article is "Innovative development of Ukraine and Ivano-Frankivsk in the war period". The article is dedicated to identifying the main trends and features of the innovative development of Ukraine and Ivano-Frankivsk during the war period, and this is the novelty of the work. To carry out the research in the scientific work, the following methods were used: analysis and synthesis - to analyze the innovative development of Ukraine, tabular method - to analyze the leaders of innovative economies by income groups, statistical analysis - to evaluate the innovative capacity of Ukraine for 2019-2023, graphic - for visualization conclusions. It has been proven that the military actions on the territory of Ukraine significantly increased the processes of degradation of innovative transformations in Ukraine. A review of analytical information shows that Ukraine has "decreased" in its innovative development indicators compared to 2019, which indicates a decrease in innovative and scientific and technological activity. However, since 2022, there has been an improvement in this direction. It is assumed that the growth of innovative activity was caused by the full-scale war of Russia against Ukraine, where Ukraine must find innovative approaches, solutions for the relocation of businesses from the combat zone, and develop and implement innovations on the battlefield. The justified relevance of the development of the concept of the city of the future, where innovations are realized in the form of a Smart city. Such a city not only becomes a platform for technological achievements, but also promotes an active exchange of information between the scientific community and residents. In this context, Ivano-Frankivsk with the urban laboratory "Metalab", the platform "Teple Misto", the innovation center "Promprylad. Renovation" is a very favorable city for the development of innovative business. This is especially relevant at a time when a large number of enterprises from the East and Center are relocating to the West of Ukraine. It is well-founded that initiatives such as Metalab are a key aspect of modern urban development. They reflect an inclination towards an innovative approach in solving problems and creating a comfortable environment for residents in cities. Metalab is both a community united by an interest in city life, a desire to learn and improve the urban environment, and a physical platform for communication, urban research and events, whose projects intersect and reinforce each other. It has been proven that Metalab actively contributes to the development of the city through its projects. It was noted that the "New Economy of Ivano-Frankivsk" project, implemented through Metalab, is an important step towards the development of innovative activity in Ivano-Frankivsk. This project, with the help of a partnership with the city executive committee and other partner organizations, is actively engaged in promoting the idea of an innovative space in the city, and to further improve the communication between entrepreneurs and scientists, which will lead to the development of creative ideas and facilitate doing business. In general, this contributes to the improvement of the economic situation in Ivano-Frankivsk, which confirms the practical significance of the work.